Implementasi Kebijakan Sistem Zonasi Penerimaan Peserta Didik Baru Tingkat SMP di Kabupaten Bogor - Muhamad Husein Maruapey; Saprudin; M. Rifa’i Eka Pratama; Asep Noor By; Kiki Rizki Fauzi; Muhammad Rudy Herliansyah; M. Agil Setiawan; Saprudin, Saprudin (Sawala : Jurnal Administrasi Negara, 2024)
Education is fundamentally important and greatly needed by every citizen, and education must be implemented evenly and fairly for every citizen because enriching the nation's life is one of the goals of the Republic of Indonesia. The policy of the zoning system for the New Student Admission (PPDB) initiated by the government is an effort to reduce the gaps between schools that are categorized as superior and those that are not yet superior. This research was conducted to determine the success of the implementation of the zoning system policy for PPDB at the junior high school level in Bogor Regency, as well as the challenges faced and the efforts made by policy implementers. The method used was descriptive qualitative method with George C. Edward III's theory focusing on four dimensions: Communication, Resources, Disposition, and Bureaucratic Structure. The implementation success of the SAMISADE program in Megamendung Village has been observed to be effective, evidenced by in-depth interviews with informants, supporting documents, and the results of the zoning system implementation for PPDB at the junior high school level in Bogor Regency. Key words: Implementation, Public Policy, Zoning System PPDB.